2023
DOI: 10.1002/chem.202301619
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Electrocatalysts in Urea Production

Abstract: Urea synthesis from abundant CO2 and N‐feedstocks via renewable electricity has attracted increasing interests, offering a promising alternative to the industrial‐applied Haber‐Meiser process. However, the studies toward electrochemical urea production remain scared and appeal for more dedications. Herein, in this perspective, up‐to‐date overview on the urea electrosynthesis is highlighted and summarized. Firstly, the reaction pathways of urea formation through various feedstocks are comprehensively discussed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Among such methods, the electrocatalytic approach stands out. Over recent decades, the electrochemical synthesis of urea has been accomplished through the coreduction of CO 2 and various nitrogenous substrates (such as N 2 , NO, and NO 3 – ). Cheng et al demonstrated an impressive feat by reporting the electrocatalytic carbon–nitrogen (C–N) coupling of N 2 and CO 2 under ambient conditions using Pd–TiO 2 electrocatalysts, achieving a urea yield rate of 3.36 mmol h –1 g –1 and a Faradaic efficiency (FE) of 8.92% . Despite this progress, the inherent chemical inertness of N 2 often results in less optimal reaction efficiencies. In contrast, NO 3 – can be activated more readily and is a common pollutant in drinking water.…”
mentioning
confidence: 99%
“…Among such methods, the electrocatalytic approach stands out. Over recent decades, the electrochemical synthesis of urea has been accomplished through the coreduction of CO 2 and various nitrogenous substrates (such as N 2 , NO, and NO 3 – ). Cheng et al demonstrated an impressive feat by reporting the electrocatalytic carbon–nitrogen (C–N) coupling of N 2 and CO 2 under ambient conditions using Pd–TiO 2 electrocatalysts, achieving a urea yield rate of 3.36 mmol h –1 g –1 and a Faradaic efficiency (FE) of 8.92% . Despite this progress, the inherent chemical inertness of N 2 often results in less optimal reaction efficiencies. In contrast, NO 3 – can be activated more readily and is a common pollutant in drinking water.…”
mentioning
confidence: 99%